2020
DOI: 10.1088/1742-6596/1457/1/012015
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of Faster R-CNN and Atrous Faster R-CNN in different distance and light condition

Abstract: This paper presents the comparison of Faster R-CNN and Atrous Faster R-CNN, which detection model, in the different distance and light condition. Also, the dataset for model training is COCO, and the classification model is residual network. The parameter for decision the performance of the model is Mean Average Precision (mAP). The results from an object resolution at 1024x768 of Faster R-CNN at 3 meters in the evening achieved mAP 1.000. Besides, the mAP at 5 meters and 8 meters were 0.798 and 0.760, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Three resolutions and two fps variants were tested, 640x480, 800x600, and 1024x768, with 15 fps and 30 fps, respectively. The three resolutions were chosen because they are standard resolutions for image processing [22], [23]. The two fps variants in the test scenario were selected because 15 fps and 30 fps are common fps choices in monitoring systems [24] and in object detection research [25].…”
Section: The System Implementation and Testingmentioning
confidence: 99%
“…Three resolutions and two fps variants were tested, 640x480, 800x600, and 1024x768, with 15 fps and 30 fps, respectively. The three resolutions were chosen because they are standard resolutions for image processing [22], [23]. The two fps variants in the test scenario were selected because 15 fps and 30 fps are common fps choices in monitoring systems [24] and in object detection research [25].…”
Section: The System Implementation and Testingmentioning
confidence: 99%
“…Machine learning (ML) is a useful tool for data visualization and management that can quickly and accurately solve a variety of problems. In previous ML research, K. Srijakkot, et al demonstrated the good performance of intruder detection in power substations with different environments and models, including a short calculation time and high accuracy [4,5]. Not only does ML has advantages in detecting intruders, but also in the medical field, where pre-processing and the IterNet model have demonstrated high accuracy in extracting retinal blood vessels [6].…”
Section: Introductionmentioning
confidence: 99%
“…This paper presented the various research issues which can be useful for the researchers to accomplish further research on crack detection. We can see from many authors used several techniques like Artificial Intelligence [7], Image Processing, Machine learning [8] or Deep learning [10] to find the cracking on the surface. However, similar works were done [9] by Elster et.…”
Section: Introductionmentioning
confidence: 99%